A Study on Moral Values Represented in Love You Till The end A Romance Movie Series - Manuel Mendonça Araujo (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This research analyzed Love You Till the End, the romance melodrama serial movie directed by Eduard Palmov - Russkoe Film Company in 2022. This research focused on the moral values in the movie. Mixed-method was applied. This study aimed to point out the moral values of the movie, and the implications of the moral values in the movie for young adults. The documentation method was used to collect the data, and the descriptive analysis technique was used to analyze the data. The findings showed that moral values such as honesty, compassion, cooperation, unconditional love and kindness are shown in the movie. Unconditional love and kindness are the most dominant moral values. The movie shares important life lessons such as critical thinking, and being aware and responsible for every little decision. The implication of these moral values is to help university students have a greater awareness of being critical and responsible before making any decision